2004
DOI: 10.1104/pp.103.033613
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Water-Soluble Chlorophyll Proteins in the Transitory Storage of Chorophyllide  

Abstract: All chlorophyll (Chl)-binding proteins involved in photosynthesis of higher plants are hydrophobic membrane proteins integrated into the thylakoids. However, a different category of Chl-binding proteins, the so-called water-soluble Chl proteins (WSCPs), was found in members of the Brassicaceae, Polygonaceae, Chenopodiaceae, and Amaranthaceae families. WSCPs from different plant species bind Chl a and Chl b in different ratios. Some members of the WSCP family are induced after drought and heat stress as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…Satoh et al (1998) proposed the water-soluble chlorophyll protein (WSCP) as a feasible candidate for a Chl carrier. However, a recent report indicated that WSCP might act as a Chlide transporter during periods of increased Chl synthesis in developing leaves rather than during Chl degradation in senescing leaves (Reinbothe et al, 2004). In higher plants, Chlorophyllase (CLH) genes encode soluble proteins that are predicted to localize in the cytoplasm, vacuole, or chloroplast stroma (Tsuchiya et al, 1999;Takamiya et al, 2000;Okazawa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Satoh et al (1998) proposed the water-soluble chlorophyll protein (WSCP) as a feasible candidate for a Chl carrier. However, a recent report indicated that WSCP might act as a Chlide transporter during periods of increased Chl synthesis in developing leaves rather than during Chl degradation in senescing leaves (Reinbothe et al, 2004). In higher plants, Chlorophyllase (CLH) genes encode soluble proteins that are predicted to localize in the cytoplasm, vacuole, or chloroplast stroma (Tsuchiya et al, 1999;Takamiya et al, 2000;Okazawa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Satoh et al (1998) proposed the water-soluble chlorophyll protein (WSCP) as a feasible candidate for a Chl carrier. However, a recent report indicated that WSCP might act as a Chlide transporter during Chl synthesis in developing leaves rather than during Chl degradation in senescing leaves (Reinbothe et al, 2004). In higher plants, Chlorophyllase (CLH) genes encode soluble proteins that are predicted to localize in the cytoplasm, vacuole, or chloroplast stroma (Tsuchiya et al, 1999;Takamiya et al, 2000;Okazawa et al, 2006).…”
Section: Regulation Of Chlorophyll Degradationmentioning
confidence: 99%
“…A water-soluble chlorophyll protein (WSCP) was recently discovered for barley etiochloroplasts [52] that displays similarity to WSCPs of Brassicaceae [41]. Interestingly, in cauliflower WSCPs bind both Chl a and Chl b but exhibited pigment fluorescence at 680 nm only when present in a homo-oligomeric state [41].…”
Section: Light-induced Disintegration Of Lhpp During Natural Greeningmentioning
confidence: 99%
“…barley WSCP is a nucleus-encoded plastid protein which is synthesized as a 27 kDa precursor. Import into the plastid occurs under conditions when Chlide is produced, and the 27 kDa precursor is processed to mature size of 22 kDa [52].…”
Section: Pigment Binding To Wscps and Photosystem II Core And Antennamentioning
confidence: 99%
See 1 more Smart Citation